ANALISIS TIPE KEPEMIMPINAN PADA KOMANDAN DAN WAKIL KOMANDAN RESIMEN MAHASISWA BATALYON 041/INDRABUANA UNIVERSITAS RIAU - Dedi Devit Simbolon; Zahirman Zahirman; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the Types of Leadership of theCommander and Deputy Commander of Battalion 041 / Indrabuana University StudentRegiment, Riau University. The formulation of the problem in this study is What is thetype of leadership of the Commander and Deputy Commander of the Student Regimentin the University of Riau Student Regiment UKM. This research uses a qualitativeapproach. The informants examined using the Snowball sampling technique were theRiau University Student Regiment Commander, Deputy University Regiment StudentCommander, Head of Operations Section III, Head of Section IV Logistics, andMembers of the Riau University Student Regiment. Data collection techniques arecarried out through observation, interviews and documentation. Data analysistechniques using data collection, data reduction, data presentation, and conclusions.Based on the results of the research conducted, it can be concluded that the Type ofLeadership in the Commander and Deputy Commander of Battalion 041 / IndrabuanaUniversity Students in Riau University is a type of militarized leadership which is a typeof leader who has high discipline and usually likes formal matters. Implement acommand system in moving subordinates to carry out orders.Key Words: Analysis, Leadership Type